Revisiting Metropolitan Governance: Improving the Delivery of Urban Services through Inter-LGU Cooperation - Marife Magno-Ballesteros; Elmer S. Mercado; Amillah Rodil-Ocampo; Tatum P. Ramos; Pauline Joy M. Lorenzo; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2023)
Interlocal cooperation has long been promoted in the Philippines to address resource limitations of local government units; however, there is a lack of discussion on how it can efficiently deliver urban services. This study aims to investigate models of cooperation in the delivery of critical urban services through an evaluation of the management structure, financing strategies, sustainability, and issues/challenges of the interlocal arrangement in relation with operationalization. It focuses on answering the following policy questions: (1) what forms of interlocal cooperation have been utilized in the delivery of urban services; (2) how has interlocal cooperation improved the delivery of urban services; and (3) how can interlocal cooperation work better and be sustained given the decentralized nature of local politics. A closer look through findings from desk reviews and interviews is given to solid waste management and healthcare since they have been identified as services wherein cooperation among LGUs extensively developed. Reforms are then proposed to improve the effectiveness of interlocal cooperation in efficiently delivering urban services.
Keywords: 330; interlocal cooperation; Mandanas-Garcia Supreme Court Ruling; metropolitan arrangement; solid waste management; healthcare